2.2. Social Work in Spain - Juan Toset, Eva María; Zanón Bayón-Torres, Laura María (My University, 2023)
.

Social work in Spain focuses on migrant and refugee populations through training, awareness campaigns, and ethical guidelines. However, there's no specific agenda for this within social work institutions. While the Code of Ethics emphasizes diversity and non-discrimination, it lacks specific guidance on cultural competence. Social work practice includes various areas like reception, integration, and legal guidance, but lacks a unified approach. Research on migration in social work is growing, covering inclusion/exclusion processes and policy analysis. Effective intervention requires cultural awareness, understanding of power dynamics, and recognition of institutional challenges in addressing global migration issues.
Monografía